2022
DOI: 10.1039/d2ta02255a
|View full text |Cite
|
Sign up to set email alerts
|

MXene in core–shell structures: research progress and future prospects

Abstract: MXene is an emerging two-dimensional (2D) material whose properties have been well-evaluated to cater to a wide range of applications. However, the challenge of using MXenes is acquainted with its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 206 publications
0
17
0
Order By: Relevance
“…As categorized in the dimensional growth of structures, the formation of 0D, 1D, 2D, and 3D structures are widely investigated in the mechanistic formation of crystals and their morphology [62][63][64][65][66]. Tiwari et al [67] categorized different nanostructured materials as 0D, such as uniform particles arrays (quantum dots), heterogeneous particles arrays, core-shell quantum dots, onions, hollow spheres, and nanolenses; 1D such as nanowires, nanorods, nanotubes, nanobelts, and nanoribbons; 2D such as junctions (continuous islands), branched structures, nanoprisms, nanoplates, nanosheets, nanowalls, and nanodisks; and 3D such as nanoballs (dendritic structures), nanocoils, nanocones, nanopillars, and nanoflowers.…”
Section: Nature-inspired Structures: Synthesis Structural Formation A...mentioning
confidence: 99%
See 1 more Smart Citation
“…As categorized in the dimensional growth of structures, the formation of 0D, 1D, 2D, and 3D structures are widely investigated in the mechanistic formation of crystals and their morphology [62][63][64][65][66]. Tiwari et al [67] categorized different nanostructured materials as 0D, such as uniform particles arrays (quantum dots), heterogeneous particles arrays, core-shell quantum dots, onions, hollow spheres, and nanolenses; 1D such as nanowires, nanorods, nanotubes, nanobelts, and nanoribbons; 2D such as junctions (continuous islands), branched structures, nanoprisms, nanoplates, nanosheets, nanowalls, and nanodisks; and 3D such as nanoballs (dendritic structures), nanocoils, nanocones, nanopillars, and nanoflowers.…”
Section: Nature-inspired Structures: Synthesis Structural Formation A...mentioning
confidence: 99%
“…The construction and design of 1D nanoarchitecture and the flexibility of binder-free electrode material have shown great interest for electrode fabrication. The practical capacitance and stability of the metal oxide greatly depend on the composition, synthesis condition, and morphology of the structure [43,63,112,113,114,115,116,117]. Manikandan et al [118] designed binder-free vanadium oxide spider web-like nanostructure by using facile in situ hydrothermal technique for SSC devices.…”
Section: Spider Web-like Structurementioning
confidence: 99%
“…Several reviews have been reported on the emerging MXene and LDH materials and their combination with various 0D, 1D, and 2D materials. [51][52][53][54][55][56][57][58][59] The progress of Ti 3 C 2 MXene/LDH nanocomposites has also been recently summarized, highlighting the synthetic methods, properties, and applications of such MXene-based hybrids. 60 However, as far as we know, no critical review yet explicitly investigates the electronic interactions at the interface between these two 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous depletion of fossil fuel has motivated researchers to seek clean, green, and long lasting alternative resources for energy related applications. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Due to their extended cycle life, high power density, and Coulombic efficiency, as well as low maintenance requirements, supercapacitors (SCs) are being hailed as promising energy storage systems. [15][16][17][18][19][20][21] Higher demands are put on today 0 s state-of-the-art supercapacitors in the areas of electrochemical performance, fabrication cost, sustainability, environmental friendliness, and intelligent application because they are being seen as a dominant energy-storage technology to sustainably power various portable electronics and large electric vehicles in our modern society.…”
Section: Introductionmentioning
confidence: 99%